Paradoksy komunikacji szkolnej - rozważania na temat wybranych ograniczeń rozwoju kompetencji komunikacyjnych uczniów we współczesnej szkole - Kuszak, Kinga (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2013)
The article points to the features of classroom communication which hinder the development of students’ communicative competences. The author describes the paradoxes of classroom communication reflected in the fact that the teachers enjoy significantly more rights and privileges than the students with regard to both the form and the content of the messages they express, as well as the paradoxes stemming from the artificial, formalized language present in the classroom, which actually hinders the development of communicative skills.
The Paradoxes of Classroom Communication. On Selected Limitations of Communicative Competence Development in Contemporary School Students
Keywords: communicative competence; classroom communication; low competence level; teacher-student relationship